2022
DOI: 10.3127/ajis.v26i0.3239
|View full text |Cite
|
Sign up to set email alerts
|

Saving the environment from the internet: A polynomial mitigation model of reducing Individual Internet Consumption through Internet Pricing and Environmental Awareness

Abstract: The ever-increasing internet usage purports to make substantial damage to the environment as a result of the emissions arising from the internet supporting infrastructures like data centers. However, there has been much less discussion on creating an awareness of the damage that the internet does to the environment. The purpose of this study is to investigate whether the internet use can be reduced at the individual level by calibrating internet price and one’s environmental awareness. The study employs a popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 117 publications
0
3
0
Order By: Relevance
“…Some findings demonstrate that increased awareness helps people translate their intentions into actions (Chatzisarantis & Hagger, 2007). Wathuge and Sedera (2021) , who examined internet use and awareness in a longitudinal study, found that awareness alone can change behavior. In contrast to these findings, Greisel et al (2023) hypothesized that a model developed from TPB might describe evidence-informed reasoning in pre-service teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Some findings demonstrate that increased awareness helps people translate their intentions into actions (Chatzisarantis & Hagger, 2007). Wathuge and Sedera (2021) , who examined internet use and awareness in a longitudinal study, found that awareness alone can change behavior. In contrast to these findings, Greisel et al (2023) hypothesized that a model developed from TPB might describe evidence-informed reasoning in pre-service teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Krause et al [106] show that receiving positive feedback from others or using media to reflect on one's own self are mainly associated with benefits for users' self-esteem, which consequently increases the relatedness need. We used the study findings of Wathuge and Sedera [107,108] to satisfy the relatedness need.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…However, Loock et al [17] state that studies at the individual level are also important because individual behaviors on a wide scale also have a considerable impact on the quality of the environment. Although individual-level technical steps such as human-computer-interaction designs [18,19] and gamification techniques [20] have been investigated, non-technical self-regulated and non-self-regulated interventions in reducing internet pollution have been not studied [21]. Hence, this study aims to fill that gap by aiming to identify the effect motivation and price interventions have on individuals' willingness to reduce internet usage.…”
Section: Introductionmentioning
confidence: 99%